2003
DOI: 10.1521/scpq.18.2.206.21861
|View full text |Cite
|
Sign up to set email alerts
|

The developmental context of school satisfaction: Schools as psychologically healthy environments.

Abstract: A positive psychology perspective on school psychology challenges us to think critically about the degree to which schools and schooling processes support children's optimum adjustment. We argue that schools contribute to a student's positive adjustment when they function as psychologically healthy environments for development. In this narrative review, we examine contemporary perspectives on positive adjustment in children and propose a developmental-ecological perspective as one theoretical lens through whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
129
1
18

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(172 citation statements)
references
References 59 publications
(74 reference statements)
11
129
1
18
Order By: Relevance
“…Making comparisons between these findings and adult happiness literature is difficult, however, several studies examining youth happiness (Baker, Lilly, Aupperlee & Patil, 2003;Park & Peterson, 2006;Proctor, Linley & Maltby, 2009) parallel trends indicated in this study. Gilman and Huebner (2006) revealed that youth (from Yr 6-12) reporting high levels of life satisfaction were more likely to have positive relationships, less intrapersonal stress, higher levels of hope and personal control than those with low life satisfaction; positive affirmations in the PH2 appear indicative of these individuals.…”
Section: Student Behaviour and Happinesssupporting
confidence: 64%
“…Making comparisons between these findings and adult happiness literature is difficult, however, several studies examining youth happiness (Baker, Lilly, Aupperlee & Patil, 2003;Park & Peterson, 2006;Proctor, Linley & Maltby, 2009) parallel trends indicated in this study. Gilman and Huebner (2006) revealed that youth (from Yr 6-12) reporting high levels of life satisfaction were more likely to have positive relationships, less intrapersonal stress, higher levels of hope and personal control than those with low life satisfaction; positive affirmations in the PH2 appear indicative of these individuals.…”
Section: Student Behaviour and Happinesssupporting
confidence: 64%
“…Regarding school satisfaction and its relation to self-esteem, previous research has only found weak relationships (Baker, Dilly, Aupperlee & Patil, 2003) and the results obtained here also indicate a weak relationship between Global School Satisfaction and Self-Esteem, and also between Global School Satisfaction and most of the other indicators of childhood adaptation. What could then contribute to the high school satisfaction of these children?…”
Section: Childhood Findingssupporting
confidence: 56%
“…The strongest (but still moderate) correlations are to the teachers' ratings (e.g Harmony and School Motivation). Maybe the relationship with some of the teachers' ratings could be interpreted as markers for the importance of a good teacher-student relationship for school satisfaction (Baker et al, 2003). Further, the low Timidity score in the most positive cluster can be understood as describing outgoing, open and extraverted children.…”
Section: Childhood Findingsmentioning
confidence: 99%
“…Although there is a recent growing interest in emotional and affective dynamics in teacher-student relationships, the literature is still scant (Sakiz, 2007). In recent studies, educational researchers have placed great emphasis on the influence of teacher practices, attitudes, and support on students' academic, behavioral, and psychological functioning (Baker et al, 2003). Although social and expressive support involved several affective support dimensions, the complete investigation of teacher affective support has not yet been pursued.…”
mentioning
confidence: 99%